Effectiveness of a single dose of Japanese encephalitis vaccine among adults, Assam, India, 2012–2018. Issue 35 (16th August 2021) - Khan, Siraj A.; Choudhury, Parveena; Kakati, Sanjeeb; Doley, Rimamoni; Barman, Manash P.; Murhekar, Manoj V.; Kaur, Harpreet
Highlights: Vaccine effectiveness (VE) of single dose of JE vaccine was evaluated among Indian adults. Vaccine provided adequate protection for at least six years. A significant reduction in incidence of JE among adults was noted. However, coverage of vaccine was low. Periodic mass vaccination campaigns will further reduce the disease burden. Abstract: Background: Japanese encephalitis virus (JEV) remains the major etiology of encephalitis throughout Asia. In India, the state of Assam alone contributes more than one-third of the national burden of JE. Between 2011 and 2014, a single dose of JE vaccine SA 14-14-2 (LAJEV) was administered among adults aged 15–65 years residing in Sivasagar and Dibrugarh districts of Assam, India. We monitored the trend of JE incidence between 2009 and 2018 using JE surveillance data, estimated the long-term effectiveness of the single dose of LAJEV and estimated the coverage of JE vaccine in two districts. Methods: We compared the JE vaccination status of laboratory-confirmed hospitalized JE patients (case) and age, sex and locality matched healthy individuals (controls) to estimate the effectiveness of single dose of JE vaccine. We used surveillance data for 2009–2018 to calculate the incidence of JE among adults. We conducted a community-based survey to estimate the coverage of JE vaccine in the two districts. Results: A total of 452 laboratory-confirmed JE case-patients and 904 matched healthy controls were enrolled in the study between 2012 and 2018. The effectiveness of a single dose of JE vaccine over the 7-year period was 77.0 (95% CI: 67.0–83.0). Vaccine effectiveness decreased from 91% (95% CI: 73.0–97.0) in first year of vaccination to 71% (95% CI: 21.0–90.0) at six years post-vaccination. The incidence of adults JE cases declined from 10.5 per 100, 000 in the pre-vaccination period to 5.7 per 100, 000 in the years following vaccination. The coverage of vaccine among adults in two districts was 40.1% (36.8–43.5). Conclusions: A single dose of JE vaccine offered adequate protection for at least six years. Conducting mass vaccination campaigns periodically would further reduce the incidence of JE in endemic districts in Assam.